Change in Neuroticism and Extraversion among Pre-University Education Employees during the COVID-19 Pandemic - Teodora-Gabriela Alexescu; Mădălina-Stela Nechita; Anca-Diana Maierean; Damiana-Maria Vulturar; Mircea Ioan Handru; Daniel-Corneliu Leucuța; Olga Hilda Orășan; Vasile Negrean; Lorena Ciumarnean; Doina Adina Todea (Medicina, 2022)
Background and objectives: Since the first reports of SARS-CoV-2 infection cases in China, the virus has rapidly spread to many countries, including Romania. In Romania, schools were closed in March 2020 to prevent the virus from spreading; since then, they have been sporadically opened, but only for a short time. Teachers had to adopt online education methods, experiencing real difficulties in their attempts to maintain high-quality teaching, as a result of social distancing from students and colleagues. The current study aimed to evaluate the burden on the neuroticism states of employees in the pre-university education system during the COVID-19 pandemic. Materials and Methods: A prospective study was conducted, in which personality trait data from 138 employees were collected via a questionnaire (EPI, Eysenck Personality Inventory), which measured extraversion–introversion and neuroticism scores before and during the COVID-19 pandemic. Initially, 150 subjects were invited to participate in the study, although 12 of them refused to participate. Based on the questionnaire not being fully filled in a further three subjects were excluded from the study, leaving a total of 135, of which 115 were woman and 20 were men. Results: The results demonstrate that the subjects included in the study expressed higher neuroticism during the COVID-19 pandemic than in the pre-pandemic period. This change could promote more stress and depression symptoms. Subjects with high school education had significantly lower neuroticism scores over time than those with university education (p = 0.006). Furthermore, we found extraversion scores to be statistically significant in our population (p = 0.022). Conclusion: The gender and living environment of the teachers were not significantly associated with the reduction in the extraversion score, but were more frequently found among older persons and in subjects without higher education. Subjects of Hungarian ethnicity had lower extraversion scores than those of Romanian ethnicity.